Post Ictal Psikosis Berulang pada Penderita Epilepsi - Shinta Kusumawati; Rima Zakiyah (JIMR - Journal of Islamic Medicine Research, 2017)
Post ictal psychosis (PIP) is a type of psychosis as a chronic complication of chronic epilepsy. Postictal psychosis is characterized by lucid intervals and episodes of psychosis occur within 7 days after seizure. Reported by a 23-year-old man who was consulted to a neurology department with psychosis accompanied by previous seizure history. Of heteroanamnesa obtained awareness of the consciousness changed since 6 hours before entering the hospital and history of seizures of whole body 2 days earlier, similar complaints occurred 2 and 3 years ago. Physical examination and normal neurological status, psychiatric status acquired consciousness changed, impaired thinking process, decreased will and psychomotor increased. EEG results show abnormal 3. Psychosis improved within 5 days MRS. PIP can be prevented during a controlled seizure, but recurrent PIPs are at risk of becoming Schizophrenia Like Psychosis of epilepsy.Key words: post ictal psychosis, seizure, psychosis, lucid interval